2017
DOI: 10.3758/s13423-017-1316-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociomotor action control

Abstract: Our actions affect the behavior of other people in predictable ways. In the present article, we describe a theoretical framework for action control in social contexts that we call sociomotor action control. This framework addresses how human agents plan and initiate movements that trigger responses from other people, and we propose that humans represent and control such actions literally in terms of the body movements they consistently evoke from observers. We review evidence for this approach and discuss comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 134 publications
5
66
0
Order By: Relevance
“…Recent studies have begun to investigate whether effectbased action control also extends to the behavior of other agents as possible action effects-so-called sociomotor actions (Kunde, Weller, & Pfister, 2017; for corresponding empirical findings, see Flach, Press, Badets, & Heyes, 2010;Kunde, Lozo, & Neumann, 2011;Müller, 2016;Pfister, Dignath, Hommel, & Kunde, 2013). In the study of , two participants worked in pairs.…”
mentioning
confidence: 99%
“…Recent studies have begun to investigate whether effectbased action control also extends to the behavior of other agents as possible action effects-so-called sociomotor actions (Kunde, Weller, & Pfister, 2017; for corresponding empirical findings, see Flach, Press, Badets, & Heyes, 2010;Kunde, Lozo, & Neumann, 2011;Müller, 2016;Pfister, Dignath, Hommel, & Kunde, 2013). In the study of , two participants worked in pairs.…”
mentioning
confidence: 99%
“…Although many studies have focused on the sense of agency during motor actions (e.g., Chambon, Sidarus, & Haggard, 2014), less is known about this phenomenon in social interactions. Consistent with hypothesized models that ascribe the experience of agency to the ability to link the action to the corresponding outcomes (Blakemore, Wolpert, & Frith, 2000), a similar connection can be expected for social responses of another person after initiating a social action (Friston & Frith, 2015;Kunde, Weller, & Pfister, 2018;Wolpert, Doya, & Kawato, 2003). In this article, we will refer to the concept of agency within a social interaction as social agency (Brandi, Kaifel, Bolis, & Schilbach, 2019;Recht & Grynszpan, 2019).…”
mentioning
confidence: 53%
“…Anticipation. The sociomotor framework (Kunde et al, 2018) postulated that much of the anticipation observed in social interactions can be attributed to a general mechanism that governs actions in individual and social contexts alike. In this view, actions are represented in terms of their effects, so executing an action in a social context involves anticipating the response that this action typically evokes in others.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, participants are known to initiate a button-press more quickly when it is followed by a spatially compatible light effect (e.g., a right button-press followed by a light on the right side), as compared to an incompatible light effect (e.g., a right button-press followed by a light on the left side; Kunde, 2001; see also Horváth, Bíró, & Neszmélyi, 2018;Kunde, Koch, & Hoffmann, 2004;Pfister, Janczyk, Wirth, Dignath, & Kunde, 2014). Importantly, the sociomotor framework (Kunde et al, 2018) holds that such mechanism of action planning can be extended to social interactions, i.e., an action can also become associated with the behavior that it typically evokes in others. Under this premise, agents may represent their action in terms of the expected response of their interaction partner, and therefore, in social contexts, action execution should come with an anticipation of the partner's upcoming response.…”
mentioning
confidence: 99%
See 1 more Smart Citation